Pelatihan kader tentang pengenalan hipertensi dan preeclampsia di wilayah pesisir desa Sawa Kebupaten Konawe Utara : Cadre training on the recognition of hypertension and preeclampsia in the coastal area of ??Sawa village, North Konawe Regency - Hikmandayani, Hikmandayani; Aisa, Sitti; Khair Anwar, Khalidatul (Jurnal Inovasi, Pemberdayaan dan Pengabdian Masyarakat, 2024)
Background Hypertension is a common disease that is defined simply as an increase in blood pressure. This disease can be the cause of high morbidity and mortality rates for both mothers and fetuses/babies born. Hypertension during pregnancy can develop unexpectedly and quickly become severe hypertension. As many as 61% of women with gestational hypertension experience disease progression to severe hypertension and are at risk of developing cerebrovascular disorders. Preeclampsia is defined as new onset of persistently elevated BP (BP? 140mmHg or BP? 90mmHg) and occurring after 20 weeks of gestation accompanied by one of the following complications; proteinuria, thrombocytopenia, renal impairment, liver impairment, or pulmonary edema. Training methods, educative and participatory outreach, targeting health cadres, in the form of training on blood pressure checks and health education, health education provided regarding danger signs and risk factors for pregnant women regarding hypertension and preeclampsia in pregnant women. Results. The results of univariable analysis regarding the age of pregnant women showed that of the 30 participants, 60% (18 people) were of productive age, namely 20-35 years, the remaining 40% (12 people) were over 35 years old. The level of education shows that there are still 13% (4 people) of respondents who only received junior high school education and 77% (23 people) who graduated from junior high school and 10% (3 people) of respondents whose education reached higher education. ). The average value of knowledge for pregnant women during the pretest was 58.00 (good enough category according to Arikunto), while all participants experienced an increase in knowledge with an average of 90.00 (good category according to Arikunto) after being given the post test. The conclusion was that the cadre training on hypertension and preeclampsia in pregnancy went smoothly, all participants were very enthusiastic about participating in the activity. It can be seen from the number of cadre participants who participated and the increase in knowledge was also very significant.